The Teacher Professionalism: The Biblical Study of Teacher Professionalism Phenomena - Aprilia Sungamta; Laura Manullang; Indah Gresia Tampubolon; Tri Putri Handayani; Rahel Simbolon; Natalia Silalahi (PT. Global Research Collaboration, 2024)
Education is the main foundation in creating an advanced, dignified, and competitive society. As one of the key elements in the education process, teachers have an irreplaceable strategic role. The purpose of this study is to provide a comprehensive overview of the current state of teacher professionalism, while also offering recommendations that can be used by policy makers in designing effective teacher development programs. In addition, this study is also expected to be a reference for educators in reflecting on and improving the quality of their professionalism in accordance with the demands of the times. This study uses a library search approach (library research). This research method aims to provide an overview of teacher professionalism based on data obtained through literature reviews and primary data from respondents. The results of the study indicate that teacher professionalism at SMA Negeri 5 Sungai Penuh still has several significant shortcomings. The results of the questionnaire showed that the majority of teachers have a good understanding of professionalism, especially in the dimensions of pedagogical and professional competence. The conclusion of this study is Most teachers have shown a good level of professionalism, especially in pedagogical and professional competence.